2011
DOI: 10.1371/journal.pone.0025903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Context upon Functional Connectivity during Observation of Biological Motions

Abstract: The aim of this study was to examine brain responses, in particular functional connectivity, to different visual stimuli depicting familiar biological motions. Ten subjects actively observed familiar biological motions embedded in point-light and video displays. Electroencephalograms were recorded from 64 electrodes. Activity was considered in three frequency bands (4–8 Hz, 8–10 Hz, and 10–13 Hz) using a non-linear measure of functional connectivity. In the 4–8 Hz and 8–10 Hz frequency bands, functional connec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
0
7
1
Order By: Relevance
“…A recent study by Hars et al (2011) provided corroborative neuroimaging evidence for the modulating effects of attention on neural activity in brain regions subserving biological motion perception and action understanding. They had participants who were trained gymnasts watch either naturalistic videos of an expert perform acrobatic gymnastic movements or relatively impoverished point-light displays of the same movements, recorded with a motion capture system and from the same expert.…”
Section: Neuroimaging Studiesmentioning
confidence: 86%
“…A recent study by Hars et al (2011) provided corroborative neuroimaging evidence for the modulating effects of attention on neural activity in brain regions subserving biological motion perception and action understanding. They had participants who were trained gymnasts watch either naturalistic videos of an expert perform acrobatic gymnastic movements or relatively impoverished point-light displays of the same movements, recorded with a motion capture system and from the same expert.…”
Section: Neuroimaging Studiesmentioning
confidence: 86%
“…The present results point to an element specifically contributing to facial expression processing within this social brain system. Moreover, the unfolding of affect expression in a face is inseparably linked to biological motion (hand, face, or body), detection of which has been found to activate superior temporal sulcus (STS; e.g., Hars et al, 2011;Thompson, Hardee, Panayiotou, Crewther, & Puce, 2007), even in tasks requiring emotion processing like theory of mind (Frith & Frith, 1999;Krakowki, Ross, Snyder, Sehatpour, Kelly, & Foxe, 2011;Sugranyes et al, 2011). No study seems to have examined biological motion and its cortical correlates specifically in SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al (2011) found that stimuli showing moving hands or nomovement social interaction prompted less 8-to 13-Hz suppression (ERD) over sensorimotor cortex in first-episode schizophrenia patients than in controls. In healthy volunteers, Hars, Hars, Stam, and Calmets (2011) found greater 8-and 10-Hz connectivity for sensorimotor cortex during the observation of biological motion. In addition, electroencephalographic (EEG) and magnetoencephalographic (MEG) findings of deviantly increased or decreased baseline alpha (Ikezawa et al, 2011;Nikulin, Jönsson, & Brismar, 2012;Uhlhaas, Haenschel, Nikolic, & Sincer, 2008;Uhlhaas & Singer, 2010) suggest dysfunctional regulation of alpha oscillations in schizophrenia.…”
mentioning
confidence: 85%
“…The experimental procedure comprised two parts: an EEG recording and an interview. The first part of the experimental procedure in the present study has been described in a previous paper (Hars et al, 2011). More accurately, the current paper reports additional analysis of EEG data collected previously.…”
Section: Methodsmentioning
confidence: 99%